Consensus Mechanisms in Blockchain Networks: Analyzing Various Consensus Mechanisms Such as Proof of Work (PoW), Proof of Stake (PoS), and Practical Byzantine Fault Tolerance (PBFT) (Blockchain Technology and Distributed Systems, 2021)
Blockchain technology has revolutionized various industries by offering decentralized and secure transaction systems. A key component of blockchain networks is the consensus mechanism, which ensures agreement among nodes on the validity of transactions. This paper provides a comprehensive analysis of three prominent consensus mechanisms: Proof of Work (PoW), Proof of Stake (PoS), and Practical Byzantine Fault Tolerance (PBFT). We discuss the underlying principles, advantages, and limitations of each mechanism, along with real-world implementations. By comparing these mechanisms, we aim to provide insights into their suitability for different blockchain applications and the evolution of consensus mechanisms in blockchain networks.
Keywords: Consensus Mechanisms; Blockchain Networks; Proof of Work; Proof of Stake; Practical Byzantine Fault Tolerance; Decentralization; Security; Cryptocurrency; Distributed Ledger Technology